Hakikat Kebahagiaan: Perspektif Jalaluddin Rumi - Sahputra, Jaya; As Siddiq, Usamah (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Lhokseumawe, 2022)
Abstract: Human beings live with an orientation toward happiness. Therefore, happiness has its nuances. This research explores the nature of happiness for Muslims and non-believers from the perspective of Jalaluddin Rumi, a Sufi and the greatest mystical poet from Persia. The research is qualitative and uses literature review techniques. Primary sources such as books and research journals are used as data. This research indicates that happiness is the birthright of every human being. The problem lies within each individual, whether they want to seek happiness in this world and the hereafter, and whether they will receive the rewards of true happiness from Allah or whether Allah will provide true happiness justly to those who have not received it and make them the losers. Abstrak: Manusia hidup berorientasi kepada kebahagian. Oleh sebab itu kebahagiaan memiliki nuansa tersendiri. Penelitian bertujuan untuk mengkaji hakikat kebahagiaan seorang Muslim dan kafir dalam perspektif Jalaluddin Rumi yang merupakan seorang Sufi sekaligus penyair mistik terbesar berasal dari Persia. Penelitian berjenis kualitatif dengan teknik kepustakaan. Data dikumpulkan melalui sumber primer yang terdiri dari buku maupun jurnal hasil penelitian. Hasil penelitian menunjukkan kebahagian adalah semua manusia memiliki kebahagian hakiki masing, masalahnya ada diri setiap masing-masing insan, apakah mau mencari kebahagiaan tersebut di dunia yang kemudian di akhirat juga akan mendapat balalasan dari Allah, atau Allah yang memberikan dengan adil kebahagian hakiki tersebut kepada yang belum mendapatkan dengan menajadikannya kaum yang merugi.